1949
DOI: 10.1172/jci102084
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Development of Hypokaliemia During Therapy of Diabetic Acidosis in Juvenile and Young Adult Subjects

Abstract: It is known that hypopotassemia may appear during therapy of diabetic acidosis or coma, at times associated with muscular paralysis (1-9). This is not, however, an invariable occurrence, nor have the origins of such decreases in the serum and interstitial fluid potassium concentrations been clearly defined. It seems probable that one or more mechanisms are responsible. These include the possibilities that hypokaliemia 1 develops as a result of a continued loss of potassium in urine, that it is a manifestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1950
1950
1961
1961

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…A quantitative summary of therapy in the various age groups is shown in Table 3. These values fall within the ceiling values for waterelectrolyte administration as suggested by Talbot et al 23 E. Blood and Serum Solutes 1. On Admission: The range of hyperglycemia, the variable and frequent increases in whole blood nonprotein nitrogen, the extent of serum total CO2 decrease, the tendency to hyponatremia and hypochloremia, and the variable changes in serum potassium and inorganic phosphorus in the 0-10 mEq.…”
Section: Antecedent and Presenting Symptoms And Clinical And Laborsupporting
confidence: 84%
“…A quantitative summary of therapy in the various age groups is shown in Table 3. These values fall within the ceiling values for waterelectrolyte administration as suggested by Talbot et al 23 E. Blood and Serum Solutes 1. On Admission: The range of hyperglycemia, the variable and frequent increases in whole blood nonprotein nitrogen, the extent of serum total CO2 decrease, the tendency to hyponatremia and hypochloremia, and the variable changes in serum potassium and inorganic phosphorus in the 0-10 mEq.…”
Section: Antecedent and Presenting Symptoms And Clinical And Laborsupporting
confidence: 84%
“…Since this occurred to an equal degree when control and recovery periods of comparable length were alternated with resin periods it represented a common denominator in our experiments. The beginning and the end in each interval of the study were marked by catheterization of the urinary bladder, measurement of body weight and withdrawal of venous blood for analysis of blood nonprotein nitrogen (NPN) and sugar, and of serum carbon dioxide content, chloride, sodium, potassium, calcium, phosphorus and water, using previously described methods (5)(6)(7). The pH of anaerobic samples of serum was determined by means of the glass electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Tarail & Elkinton (25) found that depletion of intracellular potassium occurred inevitably in patients receiving no potassium because the kidney does not conserve the ion as it does those of sodium and chloride. (191) and Seldin & Tarail (192) quantitated by the balance technique the transfers of potassium which occur during the first hours of treatment when the serum potassium concentration falls from high to low levels. (24) measured the uptake of potassium by the cellular phase in patients in diabetic coma.…”
Section: Depletion Of Water and Electrolytes2mentioning
confidence: 99%